Analisa Perubahan Total Padatan Terlarut Di Pesisir Pantai Situbondo Dengan Memakai Data Citra Satelit Terra Modis - Hendrata Wibisana; Masliyah M (KERN, 2019)
Total dissolved solids which are often referred to as foreign terms Total suspended solid (TSS) is a solid particle that fills an aquatic environment where the presence of a concentration value of this TSS is a clue to the quality of a waters whether turbidity occurs or not. It is interesting to study the growth of the TSS concentration value because knowing the concentration value can be detected at the point where the growth takes place whether erosion or sedimentation. In this research, Terra Modis satellite imagery is used in 2019 and 2018 in the same month, October. The method used in this research is a remote sensing technique by carrying out statistical measurements to form a mathematical model of the wavelength of Terra Modis satellite images using visible light channels or RGB which are 412 nanometers, 531 nanometers and 667 nanometers. The results showed that the wavelength of 531 nanometers had the largest R correlation value among other RGB wavelengths, namely for the linear model the correlation value of R was 0.892 and the exponent model with an R correlation value of 0.897. The conclusion obtained from this study is that Terra Modis satellite imagery can be used to detect growth from TSS concentrations (mg / l) on the coast and also to predict growth or reduction of TSS in the future.